Antiviral effects of blueberry proanthocyanidins against Aichi virus. (September 2019) - Joshi, Snehal S.; Howell, Amy B.; D'Souza, Doris H.
Abstract: Blueberry polyphenols are known for their high antioxidant and antimicrobial potential. Aichi virus (AiV) is an emerging human enteric virus that causes gastroenteritis outbreaks worldwide. This study aimed to (1) determine the time- and dose-dependent effects of blueberry proanthocyanidins (B-PAC) against AiV over 24 h at 37 °C; (2) gain insights on their mode of action using pre- and post-treatment of host cells and Transmission Electron Microscopy; and (3) determine their anti-AiV effects in model foods and under simulated gastric conditions. AiV at ∼5 log PFU/ml was incubated with equal volumes of commercial blueberry juice (BJ, pH 2.8), neutralized BJ (pH 7.0), B-PAC (2, 4, and 10 mg/ml) prepared either in 10% ethanol, apple juice (AJ), 2% milk, simulated gastric fluid (SGF, pH 1.5) or simulated intestinal fluid (SIF, pH 7.5), and controls (malic acid (pH 3.0), phosphate buffered saline (pH 7.2), apple juice (pH 3.6) and 2% milk) over 24 h at 37 °C, followed by standard plaque assays. Each experiment was replicated thrice and data were statistically analyzed. Differences in AiV titers with 1 mg/ml B-PAC were 2.13 ± 0.06 log PFU/ml lower after 24 h and ≥3 log PFU/ml (undetectable levels) lower with 2 and 5 mg/ml B-PAC compared to AiV titers in PBS after 24 h and 3 h, respectively. BJ at 37 °C resulted in titer differences (lower titers compared to PBS) of 0.17 ± 0.06, 1.27 ± 0.01, and 1.73 ± 0.23 log PFU/ml after 1, 3, and 6 h and ≥3 log PFU/ml after 24 h. Pre- and post-treatment of host cells with 0.5 mg/ml B-PAC caused titer decreases of 0.62 ± 0.33 and 0.30 ± 0.06 log PFU/ml, respectively suggesting a moderate effect on viral-host cell binding. B-PAC at 2 mg/ml in AJ caused titer differences of ≥3 log PFU/ml after 0.5 h, while differences of 0.84 ± 0.03 log PFU/ml with 5 mg/ml B-PAC in milk, and ≥3 log PFU/ml with B-PAC at 5 mg/ml in SIF after 30 min were obtained. This study shows the ability of BJ and B-PAC to decrease AiV titers to potentially prevent AiV-related illness and outbreaks. Highlights: AiV titers can be decreased to undetectable levels with 5 mg/ml blueberry proanthocyanidins (B-PAC) after 3 h. B-PAC at 2 mg/ml in apple juice and 5 mg/ml in simulated gastric fluid can decrease AiV to undetectable levels after 0.5 h. BJ and B-PAC show potential to prevent AiV-related illness and outbreaks.